Contradiction in the novel (Symphony of the Dead) by Abbas Maroufi - Abbas, Hussein (Al-Adab Journal, 2026)
Paradox is a literary device and one of the most frequently used literary figures in literature. It occurs when a poet or writer places two contradictory words together in a meaningful connection. The combination of these contradictory words often results in an expression that does not commonly exist in the real world.Some paradoxes can be justified through mystical, religious, or philosophical interpretations. Although paradoxes are usually impossible in the external world, they enhance the beauty and imagination of literary works. Paradox contributes to the eloquence of speech. Sometimes, two words placed together may not explicitly exhibit paradoxical qualities, but when combined, they create a paradoxical meaning. In such cases, paradox may also be accompanied by irony.In general, two contradictory words must relate to a single phenomenon or concept. In other words, they should simultaneously reflect two aspects of the same entity rather than referring to two entirely different phenomena. In some instances, contradictory words may appear as possessive or descriptive compounds, or as a combination of two adjectives. In other cases, there may be a few words separating them within a sentence.In this study, we examine the use of paradox in the renowned novel Symphony of the Dead by Abbas Maroufi, one of the prominent contemporary writers.